Glutathione Antioxidant Increases Resistance of Cord Blood Nucleated Cells During Cryopreservation with Dimethyl Sulfoxide - Makashova, Olena; Mykhailova, Olga; Zubova, Oksana; Zubov, Pavlo; Babijchuk, Lubov (Problems of Cryobiology and Cryomedicine, 2020)
The cryopreservation efficiency of nucleated cells (NCs), in particular hematopoietic progenitor (HPCs) and cord blood (CB) cells was comprehensively assessed in protective mixtures, containing intracellular cryoprotectant dimethyl sulfoxide (DMSO) and antioxidant glutathione in different concentrations assessed immediately after thawing and further transfer to the in vitro conditions, simulating physiological ones. The use of 1 and 3 mM glutathione in cryoprotectant medium with 7.5 and 10% DMSO enabled preserving 85.9 and 91.2% of viable NCs and HPCs, respectively, immediately after thawing and 75–80% of viable NCs/HPCs after 1-hour incubation in the antioxidant-free Hank’s solution, which exceeded the control values. At the same time, the recovery and viability of NCs and HPCs after cryopreservation in 5% DMSO with 1mM or 3 mM glutathione were the same or even higher than those in 7.5 and 10% DMSO without glutathione. The NCs cryopreservation in the glutathione-containing solutions was established to reduce the number of DCF+ cells. The supplementation of 7.5% DMSO with 1 or 3 mM glutathione reduced the cell number with excess reactive oxygen species from 19% (in glutathione-free samples) to 11% (in glutathione-contained ones), even after transfer to the in vitro conditions, simulating physiological. Probl Cryobiol Cryomed 2020; 30(1): 058–067